Pendidikan Literasi dan Inklusi Keuangan Untuk Mewujudkan Masyarakat Berdaya Saing - Sakifah; Masitoh, Noneng; Wursan; Badriatin, Tine; Rosyadi, Agi; Rahmani, Dede Arif (LPPM Universitas Timor, 2025)
This community service activity aims to provide financial literacy and inclusion education in Putrapinggan Village, Kalipucang District, Pangandaran Regency. So far, in general, the local community still simply manages money, knowing that the function of a bank is limited as a place to save and apply for loans, both for consumptive needs and business capital. Through this PPM activity, the community receives training in good financial management, by separating the recording of business finances and personal needs. The community, some of which are also MSME actors, is starting to recognize the capital market as an investment alternative other than property, gold, or livestock and garden produce. The method used in this training is Participatory Action Research (PAR) with presentation and direct interaction involving resource persons from OJK and the West Java Region Indonesia Stock Exchange. As a result, people are getting to know various kinds of banking and capital market products, getting to know legal and illegal financial institutions, and understand the dangers of fraud or financial crimes that are increasingly rampant so they know how to prevent them.